The Operational and Financial Value of an Interventional Radiology Clinic at a Large, Academic, Tertiary Public Hospital System - McDevitt, Joseph L.; Quadri, Rehan S.; Sutphin, Patrick D.; Reddick, Mark (Journal of Clinical Interventional Radiology ISVIR, 2021)
Purpose To evaluate the operational and financial impact of an interventional radiology (IR) clinic at a tertiary county hospital system.Methods The IR clinic, which opened in January 2017, evaluates outpatient referrals and completes preprocedure workups, nonimage-guided procedures, and postprocedure follow-up visits. Procedural volumes, locations, start times, and end times were analyzed from September 2015 to June 2018, with comparison of pre- and postclinic values by t-tests.Results Relative to the preclinic period, the number of IR cases completed each quarter has increased by an average of 12% (pre: 953 ± 63, post: 1063 ± 34, p = 0.01). Procedures that saw the largest quarterly growth included port placements (44% increase; pre: 82 ± 8, post: 118 ± 17, p = 0.002), inferior vena cava (IVC) filter placements (24% increase; pre: 33 ± 12, post: 41 ± 8, p = 0.20), IVC filter removals (72% increase; pre: 18 ± 7, post: 31 ± 8, p = 0.02), and treatments of lower extremity venous disease (100% increase; pre: 7 ± 2, post: 14 ± 6, p = 0.04). Completion of 119 cases/quarter in clinic (removal of tunneled catheters and infusion ports), as well as a reduction of emergent nephrostomy exchanges, reduced quarterly facility charges for these procedures by $350,000. Since the opening of the IR clinic, the first outpatient case started 36 minutes earlier (p < 0.001) and the last case finished 19 minutes earlier (p = 0.004).Conclusion Opening an IR clinic resulted in a significant increase in case volume while reducing avoidable costs and improving efficiency of the angiography suite.
Keywords: interventional radiology; clinic-based model; public hospital systems; quality improvement